Original paperEarly and one year results of transvascular pulmonary valve implantation in patients after tetralogy of Fallot, Ross and Rastelli operations - Biernacka, Elżbieta K.; Demkow, Marcin; Śpiewak, Mateusz; Sřndergaard, Lars; Kowalski, Mirosław; Siudalska, Hanna; Wolski, Piotr; Miśko, Jolanta; Hoffman, Piotr; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background : Transcatheter pulmonary artery valve implantation (TPVI) is a relatively new method of treatment in patients (pts) after repair of congenital heart disease (CHD). Aim : To assess the early and one year results of TPVI in patients with right ventricular outflow tract conduit dysfunction. Material and methods : TPVI with routine pre-stenting with BMS was performed in 17 pts (9 men, mean age 24.1 ±5.6 years) for pulmonary conduit dysfunction 11.4 ±6.4 years after total repair of tetralogy of Fallot or pulmonary atresia (11 pts: 8 pts with pulmonary homograft, 3 pts with Contegra xenograft or aortic monocusp homograft), pulmonary stenosis (1 pt), Ross procedure (3 pts) and Rastelli operation (TGA, pulmonary atresia – 2 pts). The schedule of follow-up assessment comprised clinical evaluation, cardiovascular magnetic resonance, transthoracic echocardiography and chest X-ray to screen for device integrity. Seventeen pts completed 1-month, 11 pts 6-month and 10 pts 12-month follow-up. Results : TPVI was performed with no serious complications in all patients. In 15 patients with significant pulmonary stenosis peak right ventricular outflow tract (RVOT) gradient was reduced from a mean of 73.4 ±30.0 mm Hg to 35,3 ±14,7 mm Hg on the next day after implantation (p < 0.001). At 1-month, 6-month and 12-month follow-up mean RVOT gradient was 30.4 ±11.2 mm Hg, 31.1 ±11.9 and 32.7 ±11.7 mm Hg, respectively (NS). In all patients pulmonary valve competence was restored. Mean pulmonary regurgitation fraction decreased from 20.9 ±7.8% to 2.4 ±2.1% (p = 0.0001) one month after procedure and the effect was stable after one year observation. Significant decrease in right ventricular end-diastolic and end-systolic volumes (131.8 ±47.8 ml/m 2 to 115.3 ±40.3 ml/m 2 ; p = 0.002 and 73.1 ±41.1 ml/m 2 vs. 57,6 ±39,0 ml/m 2 ; p = 0.004, respectively) as well as a slight improvement in RV ejection fraction (47.9 ±13.0% to 53.2 ±15.2%; p = 0.07) were observed one month after procedure. No stent fractures were seen. Conclusions : 1. TPVI is an effective and safe method of non-surgical treatment for patients with RVOT conduit dysfunction. 2. TPVI wit the use of pre-stenting technique may be performed in selected patients with RVOT patch. 3. Routine pre-stenting with BMS may protect against stent fractures after TPVI. 4. The study showed excellent results in 10 patients after one-year follow-up.